Introduction to coordination, solid state, and descriptive inorganic chemistry - Rodgers, Glen E. (McGraw-Hill, 1994)
This book is an introduction to coordination, solid state, and descriptive inorganic chemistry. It is designed primarily for a sophomore inorganic chemistry audience, but could also be used as a supplementary text for some general chemistry courses. Coordination, solid state, and descriptive inorganic chemistry are each given their own self-standing sections, so that the reader can begin in any one of them without becoming frustrated at references to previously learned material. These self-standing chapters also allow you the flexibility to present material in the order you choose.